The key characteristics of mobile learning for employee's development in Kuwait workplace: a literature review - Alajmi, Nada; Md Khambari, Mas Nida; Abd Rahim, Nur Aira; Wong, Su Luan (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
The literature on mobile learning focusing on characteristics for employee’s development in the workplace usually differentiates between user experience, motivation, individuality, usability, flexibility and connectivity. Scholars highlight operationalisation, implementation, technical support and the evaluation of mobile learning environments. As stated by some authors, successful workplace learning, and mobile learning have become significant priorities in government ministries and organisations. However, the characteristics of mobile learning for employee’s development also requires an established framework that is systemic. Within the perspective of workplace learning in Kuwait, insight on the impact of adopting mobile learning can be gained from Kuwait government policies and incentives in the employee’s development. Employee training, in particular, aims at the of dissemination technological and professional abilities throughout the workplace, facilitating the continued and incremental adaptation of using mobile learning for employee’s development. The literature on Mobile learning characteristics has focused predominantly on user and technology, underestimating the effects of the traditional learning process in the workplace. Understanding the key characteristics of mobile learning is essential in supporting the employee's development in the workplace as the adoption of mobile learning encourages innovation in the workplace environment. Based on these considerations, this paper is purposed determine the key characteristics of mobile learning for employee’s development in Kuwait workplace. To achieve this, the study conducts a review of existing studies that have analysed the characteristics of mobile learning to support employee’s development. Methodical studies and proper summaries of the literature are employed to identify and categorise the results of all primary studies on the key characteristics of mobile learning for employee’s development. Considering the various variables that impact the employee's development process, theoretical contributions were explored and categorised into four study streams: mobile learning, mobile learning characteristics, workplace learning, and the Kuwait context. Our review reveals that only a few publications have focused significantly on studying the function of mobile learning in workplace learning. It also highlights the fact that the research on the employee's development through mobile learning remain few and fragmented.